A climate-fiscal policy mix to achieve Türkiye's net-zero ambition under feasibility constraints - Christian Schoder; Remzi Baris Tercioglu (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
This paper employs an estimated dynamic stochastic open-economy macro framework to identify policy interventions that allow Türkiye to achieve net-zero emissions by 2053 while respecting important feasibility constraints such as fiscal consolidation and sovereign debt stability as well as compensation of low-income households. The policy mix includes a carbon tax, a renewable energy subsidy, transfer payments, public infrastructure investments, a bad bank for stranded fossil fuel assets, and the phase-out of fossil fuel subsidies and public investment. Although the proposed policy package has only moderate effects on gross domestic product, transition risks involve declining exports and fossil asset stranding. The paper highlights the importance of transparent policy communication and a credible commitment to the net-zero agenda to ensure an orderly transition. Improving the rule of law and access to green finance considerably support the private sector-led low-carbon transition.
Keywords: Q43; Q48; 330; Bayesian estimation; Climate-fiscal policy; Low-carbon transition; Net-zero pathway; Türkiye